Benefits, Challenges, and Steps Forward on Using Poetry Workshops in Interdisciplinary Migration Research: Reflections from the Field and Methodological Insights - Nikola Lero; Jasmin Donlic; Marjan Marjanović (Societies)
This article offers a critical methodological reflection on the use of poetry workshops in migration research, positioning them as empowering, ethically complex, yet powerful research tools for studying migrant experience. While arts-based methods have gained momentum, their application often lacks critical reflexivity regarding their benefits, challenges, and interdisciplinary potential. Drawing on implementing and designing over 50 poetry workshops facilitated by the author across Bosnian/Yugoslav, U.S., and U.K. diaspora contexts, this paper employs an autoethnographic and participatory lens to explore the workshops’ dual role as sites of empowerment and tools for epistemic transformation. Beyond examining their use in participatory action research (PAR), the paper highlights how poetry workshops can serve as interdisciplinary research tools that capture not only emotional and narrative dimensions of displacement but also spatial and material aspects of migrant experience. In doing so, the paper contributes to a broader rethinking of qualitative migration research by integrating methods from the social-oriented to spatial-oriented disciplines. Ultimately, it calls for a shift from viewing poetry as an extractive technique to embracing it as a reflexive, practical research method, capable of producing richly layered, interdisciplinary knowledge about transnational migrant lives.